Umpan Balik dan Komunikasi Kesalahan terhadap Insiden Keselamatan Pasien - Lisnayana, Lisnayana; Zakaria, Radhiah; Maidar, Maidar; Abdullah, Asnawi; Hermansyah, Hermansyah (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the relationship between feedback and error communication with Patient Safety Incidents at Hospital X. The research method uses quantitative research with a descriptive-analytical design using a cross-sectional approach. The results of the study showed that health workers with good feedback and error communication never committed a Patient Safety Incident was 94.85%. While those who were less good had committed a Patient Safety Incident of 13.18%. The results of the statistical test obtained an OR value of 2.79, meaning that workers with feedback and error communication were able to prevent Patient Safety Incidents 3 times. In conclusion, there is a significant relationship between feedback and error communication with Patient Safety Incidents. Keywords: Communication, Patient Safety Incidents, Health Workers